TELAAH YURIDIS PEMBERIAN HAK GUNA BANGUNAN KEPADA PERSEKUTUAN KOMANDITER (CV) - Adhim, Nur; Mahmudah, Siti; Benuf, Kornelius (Justitia et Pax, 2020)
UUPA regulates that legal subjects to land rights, including land with the right to Building Rights (HGB), are owned by Indonesian citizens or legal entities established under Indonesian law and domiciled in Indonesia. A different thing happened when the issuance of a Circular from the Ministry of Agrarian Affairs and Spatial Planning (ATR) stated that a CV could apply for land rights in the form of HGB. The difference in the substance of the rules is the problem. This problem will be analyzed using normative juridical research methods, using secondary data, in the form of primary legal materials, and secondary legal materials. The author concludes that a CV cannot be granted a HGB certificate, because a CV is not a Legal Entity, and if it is done on behalf of another person or nominee there is a criminal threat.